2008
DOI: 10.1007/s10722-008-9319-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological spike diversity of Omani wheat

Abstract: Little is known about the diversity of field crops in Oman. The objective of this study therefore was to characterize wheat accessions from this country using individual spikes collected from different wheat cultivation areas. The phenotypic assessment of 15 qualitative and 17 quantitative characters showed variations among Omani wheat landraces. The standardized phenotypic diversity index (H 0 ) was with 0.66 higher for quantitative characters than for qualitative characters (0.52) in tetraploid wheats and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
3
21
0
2
Order By: Relevance
“…The Shanon and Weaver index H' moyen (0.59) reflects the large morphological diversity spikes of this collection. This diversity is close to that obtained by Al Khanjari et al (2008) Concerning the result of PCA we determine the formation of two groups of characters. This reflects a positive correlation between parameters in each group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The Shanon and Weaver index H' moyen (0.59) reflects the large morphological diversity spikes of this collection. This diversity is close to that obtained by Al Khanjari et al (2008) Concerning the result of PCA we determine the formation of two groups of characters. This reflects a positive correlation between parameters in each group.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have thus focused on the characterization of traditional accessions based on agro-morphological characters (Al Khanjari et al 2008;Teklu and Hammer 2008;Surur and Amara-Hajer 2009;Zarkti et al 2012;Geleta and Grausgurber 2013), and on molecular characterization (Zarkti et al 2010;Peleg et al 2011;Oliveira et al 2012;Rekha Malik et al 2013;Medini et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to its introduction, both bread and durum wheat germplasm was subjected to evolutionary modifications as a result of natural selection and adaptation (Ali Deb et al, 1992) to the harsh desert environment prevailing in the region, and especially to the agroecological conditions of mountain and desert oases of Oman (Filatenko et al, 2010;Gebauer et al, 2010;Filatenko and Hammer, 2014). Several collecting expeditions by local (AlMaskri et al, 2003;Al-Khanjari et al, 2008) and international (Guarino, 1990) gene hunters succeeded in collecting indigenous wheat and barley (Jaradat et al, 2004) landraces, and identified rare species being conserved in situ in mountain oases. Omani wheat landraces (Triticum spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Most studies carried out on Omani crop landraces, including wheat and barley, concluded that a large and valuable diversity was available in the country and attributed this large diversity, in part, to the geographic location of the country, its physiography, as well as to germplasm exchange with its ancient trading partners in the Far East, South Asia, East Africa, especially Ethiopia through Yemen, and the larger Middle East (Harlan, 1992;Zohary and Hopf, 2000;Gebauer et al, 2010). Farmers in Oman, typical of subsistence and resource-poor farmers in wheat marginal growing regions, usually grow a mixture of locallyadapted wheat species, including tetraploid and hexploid landraces (Zhang et al, 2006;Al Khanjri et al, 2007); these mixtures occasionally result in hybrid swarms (Mastuoka, 2011) thus generating new diversity and contributing to yield buffering and stability under adverse environmental and management conditions (Al Khanjari et al, 2008). In addition, it is suggested (Zeven, 2000;Tesgaye and Berg, 2007;Karagö z and Zençirçi, 2005;Yedliay et al, 2011) that farmers grow and maintain highly variable wheat landraces to lower the risk of failure under marginal production conditions and to increase food security of isolated communities (Rijal, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation